Pengaruh Kinerja Keuangan dan Nilai Pasar terhadap Harga Saham: Studi pada Perusahaan yang Secara Konsisten Terdaftar sebagai Indeks LQ45 Selama 2020-2021 - Amalia Savitri; Dahlia Br. Pinem (Studi Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: Assessment of the company's financial performance often uses financial ratios, because financial ratios can provide information on the company's past and current financial condition. Information about financial performance has quite an effect on stock prices because it can provide an overview of the condition of the company as a whole, not only in terms of profit but in terms of assets, debt, capital, and others. This study aims to examine and analyze the effect of financial performance as assessed by Profitability, Liquidity, Solvency, and Market Value, effect on Stock Prices, because there are differences between actual and theoretical data, and there are research gaps in previous studies. The objects of this study are companies listed on the LQ 45 in the 2020-2021 period by disclosing and presenting the required data consistently registered as the LQ45 Index during the 2020-2021 period. Method: used in selecting objects in this study was purposive sampling involving 40 LQ 45 companies listed on the Indonesia Stock Exchange. The data used was panel data regression, and the Chow and Hausman tests were used to select the best test model. Result: The results showed that based on the t-test the results were obtained: the financial performance variables assessed using Profitability, Liquidity and Solvency had no effect on Stock Prices where sig > 0.05 and Market Value Variables had an effect on Stock Prices because sig < 0.005. Contribution: This information is needed by potential investors because the decision to invest requires a thorough analysis to avoid losses.